ROCKET-AF: Rivaroxaban vs Warfarin in Patients with Moderate Renal Insufficiency - Jacobson, Anne (MD Conference Express, 2011)
Patients with atrial fibrillation and moderate renal dysfunction have a higher risk of stroke and bleeding than patients with normal renal function, but respond favorably to reduced-dose rivaroxaban compared with warfarin, according to new findings from the Rivaroxaban Once Daily Oral Direct Factor Xa Inhibitor Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation [ROCKET-AF; NCT00403767].